Pressure pulsations in reciprocating pump piping systems Part 1 : modelling - Shu, Jian Jun (2011)
A distributed parameter model of pipeline transmission line behaviour is presented, based on a Galerkin method incorporating frequency-dependent friction. This is readily interfaced to an existing model of the pumping dynamics of a plunger pump to allow time-domain simulations of pipeline pressure pulsations in both suction and delivery lines. A new model for the pump inlet manifold is also proposed.